O PAPEL DA INTELIGÊNCIA ARTIFICIAL NA DETECÇÃO DE LACUNAS NO PROCESSO DE ENSINO E APRENDIZAGEM (REMUNOM, 2023)
This article addresses the application of Artificial Intelligence (AI) in detecting gaps in the teaching and learning process. AI has proven to be a promising tool in the field of education, offering advanced data analysis and interpretation capabilities to identify areas for improvement in the educational process. In this context, the detection of gaps in teaching and learning becomes crucial to promote a more efficient and personalized education, adapted to the needs of individual students. This study sought to answer the following question: What is the impact of using artificial intelligence in detecting gaps in the teaching and learning process, considering ethical challenges? This research sought to investigate the role of artificial intelligence in detecting gaps in the teaching and learning process, taking into account the ethical challenges related to the application of AI. It aims to explore the role of Artificial Intelligence in detecting gaps in the teaching and learning process. The methodology used was descriptive research through the technique of bibliographical survey of the main authors and scholars on the subject in question, in addition to information retrieved from websites and articles. It was found that Artificial Intelligence in detecting gaps in the teaching and learning process aims to use advanced data analysis capabilities to identify problem areas, adjust teaching and provide a more personalized and effective educational environment.Keywords: Artificial Intelligence, gap detection, teaching and learning, ethical challenges.